A survey of the preservation programs/practices adopted for historical collections and archival materials in selected research and academic libraries and archives in Metro Manila - Datiles, Clarita P.; Hidalgo, Namnama P.; Granda, Yolanda C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1987)
This research study investigates the status of preservation programs/practices adopted for historical collections and archival materials in major academic and research libraries and archives in Metro Manila. It also seeks to identify the types of historical collections and archival materials available in the 13 respondent institutions that participated in this survey. The libraries surveyed include the American Historical Collection (AHC); The Eugenio Lopez Foundation, Inc./Lopez Memorial Museum (ELFI/LMM); The National Library (TNL); the University of the Philippines' Jorge B. Vargas Filipiniana Research Center (UPJBVFRC); the De La Salle University Library's Filipiniana Section (DLSUL/FS); and the Ateneo de Manila University's Rizal Library Special Collections (ADMURL/SC). The archives group, on the other hand, include the Archives of the Archdiocese of Manila (AAM); the Ayala Museum Library and Iconographic Archives (AMLIA); the Philippine Province Archives of the Society of Jesus (PPASJ); the Records Management and Archives Office (RMAO); the University of the Philippines Library/University Archives and Records Center (UP/UARC); the Ateneo de Manila University Archives (ADMUA); and the University of Santo Tomas Archives (USTA). All these institutions, except for the University of the Philippines' Jorge B. Vargas Filipiniana Research Center (UPJBVFRC), have systematic preservation programs operating in their respective libraries and archives.
The study used the descriptive survey method of research. The survey questionnaire was the instrument used in gathering the data. Documentary analysis also played a major role in gathering the descriptive data of the collections found in the respondent libraries and archives.
The research findings showed that: 1) the historical collections and archival materials of the institutions surveyed consist of rare books, manuscripts, serials/newspapers, university publications, theses/dissertations, maps, sound recordings, films, mirofilms/microfiches, organizational/personal papers, photographs, and memorabilia; 2) the preservation methods employed for these materials have greatly improved compared to those used many years ago. These methods include fumigation, cleaning of documents, deacidification, restoration like tissue repair/mounting/lamination and encapsulation, microfilming/microfiching, duplicating or photocopying, binding and repair, environmental control like air-conditioning/good housekeeping practices/security measures/and control of light sources, provision for suitable storage equipment, and lastly humidity control.
Conclusion drawn from the study include the following: 1) the archives and library institutions surveyed have similar preservation programs and practices; they use practically the same preventive measures in maintaining their respective historical collections and archival materials; and 2) a lot of improvements have yet to be initiated and maintained particularly in areas like budgetary support, conservation personnel, conservation supplies and equipment, and policies and guidelines for preservations work.
In the light of the foregoing, this research study recommends the following: 1) establishment of an archives training center for the archives and library staff and those interested in conservation works; 2) acquisition of the necessary equipment and supplies; 3) provision for a substantial budget solely for conservation purposes; 4) formulation of social policies and guidelines for preservation work; 5) air-conditioning and humudity control; 6) microfilming and/or microfiching of old and deteriorating but rare Filipiniana historical items and important archival documents; and 7) formation of a "conservation consortium" for libraries and archives to better carry out definite preservation projects for their multifarious needs.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Archives--Philippines--Manila--Metropolitan area